Pre-styloid parapharyngeal space masses—Tumor margins as a predictor of benign versus malignant histology on pre-operative CT or MRI. Issue 6 (December 2022) - Vargas, Nicholas; Assadsangabi, Reza; Birkeland, Andrew; Bewley, Arnaud; Broadhead, Kenneth; Morisada, Megan; Ivanovic, Vladimir
Purpose: Evaluate the frequency of benign versus malignant masses within the prestyloid parapharyngeal space (PPS) and determine if tumor margins on preoperative cross-sectional imaging can predict malignancy status. Materials and Methods: The electronic health record at UC Davis Medical Center was searched for PPS masses surgically resected between 2015 and 2021. Cases located centrally within the prestyloid PPS with confirmed histologic diagnosis were included and separated into either benign or malignant groups. Margins of the tumors were categorized as "well defined" or "infiltrative" on preoperative cross-sectional imaging. Statistical analysis was performed to evaluate relationships between malignancy status and tumor margins. Results: A total of 31 cases met the inclusion criteria. Fourteen separate histologic diagnoses were observed. Benign cases comprised 77% (24/31) and the remaining 23% (7/31) were malignant. Pleomorphic adenoma was the most common overall diagnosis at 48% (15/31). Adenoid cystic carcinoma 6% (2/31) was the most common malignant diagnosis. Well-defined tumor margins were seen in 81% (25/31) of cases. A benign diagnosis was found in 96% (24/25) of the cases with well-defined margins. Infiltrative tumor margins were displayed in 19% (6/31) of cases, all were malignant. The sensitivity and specificity of infiltrative tumor margins for malignancy were 85.7% and 100%, respectively. The negative predictive value of infiltrative margins for malignancy was 96%. Conclusion: Infiltrative tumor margins on preoperative imaging demonstrate high specificity and negative predictive value for malignant histology in prestyloid PPS masses. Margins should therefore be considered when determining clinical management for newly diagnosed PPS tumors.